Discovery of the cicada genus Becquartina Kato, 1940 (Hemiptera: Cicadidae: Cicadinae) in India with the description of a new species from Meghalaya - Sarkar, Vivek; Thangkhiew, Rodeson; Mahapatra, Cuckoo; Mohapatra, Pratyush P.; Nair, Manoj V.; Hajong, Sudhanya R. (Zootaxa, 2024)
The genus Becquartina Kato, 1940 (Hemiptera: Cicadidae) is reported for the first time from India with a new species, Becquartina bicolor sp. nov., along with records of two distinct colour forms, from the northeastern Indian state of Meghalaya and located within the Indo-Burma Biodiversity hotspot. This paper provides an account of its natural history and bioacoustics. The present discovery extends the distributional range of the genus Becquartina from Southeast Asia into Northeast India and increases the total number of known Becquartina species to seven.